Assistance for Gari Village to Achieve Prime Village Status - Minardi; Firdaus, Mohamad; Endah Winarti, Safitri; Samaloisa, Rijel (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community Service is one of the Tri Dharma of Higher Education. After universities carry out teaching and research, they should then take real action in the form of community service. A thousand theories without realization will not bring change. However, on the contrary, if there is no further study, a thousand stories from the village are just wishful thinking. So these three are closely related and complement each other. This community service is the third service carried out by the service team for the Gari Village. The first stage emphasizes an inventory of the cultural potential that is owned. The second stage is to strengthen organizational management. So this third is the assistance of Prima Village, because Prima Village is a mandatory requirement for the Village to become a Culturally Independent Village. Assistance has been implemented for 6 months in 2024. By involving the active role of the PKK, Social Service, Women's Empowerment and Child Protection of Gunungkidul Regency and of course the Gari District Government. The target is the PKK Gari Village, Kapanewon Wonosari, Gunungkidul Regency. The aim of this service is to prepare the standard components of the Gari Village to fulfill the requirements to become a Prima Village. In the mid-service report, progress has been made: 1) equalizing the perception between the District Government and the Service Team; 2) finding the role of women in Gari; 3) determine further steps. The methods used were interviews, workshop seminars and FGD (Focus Group Discussion). Starting with conducting interviews with the Village Head and women figures, identifying problems with the PKK in the form of FGDs and holding workshops with the PKK and related departments. The article has been submitted to the Gandrung Journal from PGRI Banyuwangi University, Sinta 5